Differential Calculus Teaching through Virtual Learning Objects in the Field of Management Sciences. (20th February 2015) - Arango, Juan; Gaviria, Diana; Valencia, Alejandro
Abstract: This paper examines the use of Virtual Learning Objects (VLO) in the teaching of differential calculus in the area of Management Sciences as a teaching strategy to improve the assimilation of the theoretical knowledge acquired in the classroom courses. This is accomplished by the construction of virtual pedagogical practices concerning to optimization problems through GeoGebra. It is free software that generates VLOs with an adequate contrast between the theoretical mathematical knowledge and its practical application in Management Sciences. Thus, different dynamic, algorithmic and heuristic processes are encouraged, being useful for logic and constructivist student training. The proposed methodology is based on the construction of VLOs (Virtual Learning Objects). It allows choosing variables in the GeoGebra software where students can interact with the formulation of mathematical problems applied to their curricula. So, they strengthen their knowledge and have a greater autonomy in the analysis of optimization problems in financial and management field. The results show how these teaching strategies facilitate the assimilation of the concepts of differential calculus in Management Sciences students. This allows a greater development of student skills in front of the understanding of the geometric behaviour of a curve.